Fungal infections in mechanically ventilated patients with COVID-19 during the first wave: the French multicentre MYCOVID study. Issue 2 (February 2022) - Gangneux, Jean-Pierre; Dannaoui, Eric; Fekkar, Arnaud; Luyt, Charles-Edouard; Botterel, Françoise; De Prost, Nicolas; Tadié, Jean-Marc; Reizine, Florian; Houzé, Sandrine; Timsit, Jean-François; Iriart, Xavier; Riu-Poulenc, Béatrice; et al.
Summary: Background: Patients with severe COVID-19 have emerged as a population at high risk of invasive fungal infections (IFIs). However, to our knowledge, the prevalence of IFIs has not yet been assessed in large populations of mechanically ventilated patients. We aimed to identify the prevalence, risk factors, and mortality associated with IFIs in mechanically ventilated patients with COVID-19 under intensive care. Methods: We performed a national, multicentre, observational cohort study in 18 French intensive care units (ICUs). We retrospectively and prospectively enrolled adult patients (aged ≥18 years) with RT-PCR-confirmed SARS-CoV-2 infection and requiring mechanical ventilation for acute respiratory distress syndrome, with all demographic and clinical and biological follow-up data anonymised and collected from electronic case report forms. Patients were systematically screened for respiratory fungal microorganisms once or twice a week during the period of mechanical ventilation up to ICU discharge. The primary outcome was the prevalence of IFIs in all eligible participants with a minimum of three microbiological samples screened during ICU admission, with proven or probable (pr/pb) COVID-19-associated pulmonary aspergillosis (CAPA) classified according to the recent ECMM/ISHAM definitions. Secondary outcomes were risk factors of pr/pb CAPA, ICU mortality between the pr/pb CAPA and non-pr/pb CAPA groups, and associations of pr/pb CAPA and related variables with ICU mortality, identified by regression models. The MYCOVID study is registered with ClinicalTrials.gov, NCT04368221 . Findings: Between Feb 29 and July 9, 2020, we enrolled 565 mechanically ventilated patients with COVID-19. 509 patients with at least three screening samples were analysed (mean age 59·4 years [SD 12·5], 400 [79%] men). 128 (25%) patients had 138 episodes of pr/pb or possible IFIs. 76 (15%) patients fulfilled the criteria for pr/pb CAPA. According to multivariate analysis, age older than 62 years (odds ratio [OR] 2·34 [95% CI 1·39–3·92], p=0·0013), treatment with dexamethasone and anti-IL-6 (OR 2·71 [1·12–6·56], p=0·027), and long duration of mechanical ventilation (>14 days; OR 2·16 [1·14–4·09], p=0·019) were independently associated with pr/pb CAPA. 38 (7%) patients had one or more other pr/pb IFIs: 32 (6%) had candidaemia, six (1%) had invasive mucormycosis, and one (<1%) had invasive fusariosis. Multivariate analysis of associations with death, adjusted for candidaemia, for the 509 patients identified three significant factors: age older than 62 years (hazard ratio [HR] 1·71 [95% CI 1·26–2·32], p=0·0005), solid organ transplantation (HR 2·46 [1·53–3·95], p=0·0002), and pr/pb CAPA (HR 1·45 [95% CI 1·03–2·03], p=0·033). At time of ICU discharge, survival curves showed that overall ICU mortality was significantly higher in patients with pr/pb CAPA than in those without, at 61·8% (95% CI 50·0–72·8) versus 32·1% (27·7–36·7; p<0·0001). Interpretation: This study shows the high prevalence of invasive pulmonary aspergillosis and candidaemia and high mortality associated with pr/pb CAPA in mechanically ventilated patients with COVID-19. These findings highlight the need for active surveillance of fungal pathogens in patients with severe COVID-19. Funding: Pfizer.